Interaksi Air Tanah dan Air Permukaan Sungai Asem Ruas Antara Bendung Boreng sampai Area Industri Kabupaten Lumajang - Anisa Tri Widiyanti; Hari Siswoyo; Linda Prasetyorini (Jurnal Kridatama Sains dan Teknologi, 2026)
The interaction between groundwater and river water is an important hydrological process that affects the quantity and quality of water resources. The purpose of this study was to identify and analyze the interaction between groundwater and surface water in the Asem River in the section between Boreng weir and the Industrial Area of Lumajang Regency. The study was conducted during the dry season, namely from May to October 2025. Sampling was carried out at 5 river cross-sections, each consisting of groundwater on the left side of the river flow, surface water (river), and groundwater on the right side of the river. The physical-chemical parameters observed included pH, temperature, TDS, and EC. The measurement data were analyzed using a statistical approach that included time series analysis, correlation analysis, principal component analysis, and cluster analysis. Based on the results of the time series analysis, it can be stated that there are similarities in the fluctuation patterns of physical-chemical parameters, especially temperature and pH, between groundwater and river water. Based on the results of the correlation analysis, it can be stated that the level of relationship is moderate to strong between groundwater and river water. Based on the results of the principal component analysis, it can be stated that the TDS and EC parameters play a dominant role in differentiating water characteristics. Based on the results of the cluster analysis, it can be stated that the interaction between groundwater and river water is not uniform along the river flow, with strong interactions identified in Cross Section-4 and Cross Section-5. In general, it can be concluded that at the research location there is an interaction between groundwater and river water which is influenced by local hydrological conditions